Comprehensive genomic profiling of Finnish lung adenocarcinoma cohort reveals high clinical actionability and SMARCA4 altered tumors with variable histology and poor prognosis - Talvitie Eva-Maria; Liljeroos Lassi; Vilhonen Heikki; Orte Katri; Leivo Ilmo; Kallajoki Markku; Taimen Pekka (ELSEVIER SCIENCE INC, 2025)
Introduction: Lung adenocarcinoma is the most common type of lung cancer and typically carries a high number of mutations. However, the genetic background of the tumors varies according to patients' ethnic background and smoking status. Little data is available on the mutational landscape and the frequency of actionable genomic alterations in lung adenocarcinoma in the Finnish population.
Materials and methods: We evaluated the gene alteration frequencies of 135 stage I-IV lung adenocarcinomas operated at Turku University Hospital between 2004 and 2017 with a large commercial comprehensive genomic profiling panel. Additionally, we correlated the alterations in selected genes with disease outcomes in 115 stage I-III patients with comprehensive follow-up data. The genomic alterations in a sub-cohort of 30 never-smokers were assessed separately.
Results: Seventy percent of patients in the overall cohort and 77% in the never-smoker sub-cohort harbored an alteration or a genomic signature targetable by FDA and/or EMA approved drug for non-small cell carcinoma, respectively. In multivariable analysis for disease-specific survival, any alteration in SMARCA4 (DSS; HR 3.911, 95%CI 1.561-9.795, P = 0.004) exhibited independent prognostic significance along with stage, tumor mutation burden, and predominant histological subtypes.
Conclusions: Over two thirds of our overall cohort, and especially never-smokers had an actionable genomic alteration or signature. SMARCA4 alterations, detected in 7.4% of the tumors, independently predicted a shortened overall and disease-specific survival regardless of the alteration type. Most SMARCA4 alterations in our cohort were missense mutations associated with differentiated predominant histological subtypes and immunohistochemical SMARCA4/BRG1 and TTF-1 positive status.